Simulation of grain structure evolution during powder bed based additive manufacturing - Rai, Abha; Helmer, Harald; Körner, Carolin (Additive Manufacturing, 2017)
A lattice Boltzmann (LB) method to simulate melt pool dynamics and a cellular automaton (CA) to simulate the solidification process are coupled to predict the microstructure evolution during selective electron beam melting (SEBM). The resulting CALB model takes into account powder related stochastic effects, energy absorption and evaporation, melt pool dynamics and solidification microstructure evolution. Several physical phenomena are observed during grain solidification, e.g., initial grain selection starting at the base plate, grain boundary perturbation, grain nucleation due to unmolten powder particles in the bulk, grain penetration from the surface of the part or grain alignment dependent on the beam scanning strategy. Aim of the present work is to apply the CALB model to qualitatively examine the aforementioned phenomena. The effect of process parameters on the final grain structure and texture evolution is presented.
Keywords: Additive manufacturing; Cellular automaton; Grain structure evolution; Lattice Boltzmann method; Selective beam melting